1986
DOI: 10.1136/bmj.293.6547.587
|View full text |Cite
|
Sign up to set email alerts
|

Sleepwalking as a symptom of bulimia.

Abstract: mean duration of labour for primiparous women was less than six hours.7 Only 5% of the women had labours lasting longer than 10 hours. Afteractive management oflabour had been introduced their definition of prolonged labour was reduced from 36 hours to 12 hours. The prevalence of caesarean section varied from 4i00/o to 5-3%. The other components of active-management include the artficial rupturing of the membranes if labour does not progress according to a predetermined schedule and the use of intravenous oxyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…In addition, in our sample, parasomnias were significantly more frequent in participants meeting diagnostic criteria for a lifetime eating disorder. Several case reports and case series [35][36][37][38] have described patients who have a daytime eating disorder such as AN or BN and nocturnal eating without full awareness. Gupta 39 found that >30% of a group of patients with BN evidenced SRED.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, in our sample, parasomnias were significantly more frequent in participants meeting diagnostic criteria for a lifetime eating disorder. Several case reports and case series [35][36][37][38] have described patients who have a daytime eating disorder such as AN or BN and nocturnal eating without full awareness. Gupta 39 found that >30% of a group of patients with BN evidenced SRED.…”
Section: Resultsmentioning
confidence: 97%
“…Likewise, sleep disorders have been hypothesized to play a role in Nocturnal Eating Syndrome, although they have not been used for diagnostic purposes (Aronoff, Geliebter, Hashim, & Zammit, 1994;Guirguis, 1986;Nadel, 1981;Oswald & Adam, 1986;Schenck et al, 1991;Schenck & Mahowald, 1994). Few studies have been conducted with a large sample of patients, but various anecdotal cases have objectively confirmed the existence of Nocturnal Eating Syndrome as distinct from daytime eating disorders.…”
Section: Introductionmentioning
confidence: 92%
“…The same binge-eating episode may present during the night after sleep onset, and this behaviour may occur several times nightly. Some patients indicate full consciousness of their Nocturnal Eating Syndrome, while some indicate total amnesia (Guirguis, 1986;Gupta, 1991;Kavey, Whyte, Resor, & Gidro-Frank, 1990;Mancini & Aloe, 1994;Roper, 1989;Schenck et al, 1991;Schenck, Hurwitz, O'Connor, & Mahowald, 1993;Winkelman, 1998;Winkelman, Herzog, & Fava, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…However, only a few cases of BN purging and nonpurging type that present nocturnal eating were reported in the literature. Guirguis (1986) reported on a case of nocturnal binging in a patient with nonpurging bulimia nervosa. Williamson, Lawson, Bennett, and Hinz (1989) reported a nightly binge eating episode in a patient with purging type BN.…”
Section: Introductionmentioning
confidence: 98%